Influencing factors on attendance in cervical cancer screening among women with diabetes in Hungary: a cross-sectional study using European Health Interview Surveys 2009-2019 - Faludi Vargáné, Eszter; Ghanem, Amr Sayed; Nguyen, Chau Minh; Pataki, Jenifer; Szőllősi, Gergő József; Nagy, Attila Csaba (Frontiers in Oncology, 2025)
IntroductionWith this study, we examined the participation in cervical cancer screening among women with diabetes and the influencing factors of attendance.MethodsData from the European Health Interview Surveys in Hungary (2009, 2014, 2019) were analyzed with multivariate and multiple logistic regressions.ResultsA higher level of education (OR=2.56, 95% CI: 1.03-6.33 in the case of secondary level in 2014; and OR=3.09, 95% CI: 1.17-8.13 in the case of tertiary level in 2019, OR= 2.24, 95% CI: 1.12-4.46 in the case of tertiary level in the pooled data), a perceived good economic situation (OR=2.31, 95% CI: 1.30-4.09 in the pooled data), participation in breast cancer screening (OR= 5.41, 95% CI: 3.49-8.38 in the pooled data), and social support (OR= 2.04 95% CI: 1.03-4.03 in 2019) have a positive effect on participation in screening. Taking prescription drugs (OR= 0.31 95% CI: 0.12-0.83, in the pooled data), lower economic status (OR=0.25 95% CI:0.07-0.88, in 2009) and worse perceived health (OR= 0.20, 95% CI: 0.06-0.64 in 2014) can be considered factors with a negative effect.ConclusionThis study identified groups with low participation rates and made it clear that those groups with unfavorable health factors (bad financial status, bad perceived health, taking prescription drugs) participate the least in screening.